1978
DOI: 10.1161/01.res.42.5.628
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear proteins in the heart of the cardiomyopathic Syrian hamster. Fractionation of phenol-soluble nonhistone proteins by two-dimensional polyacrylamide gel electrophoresis.

Abstract: SUMMARY Nonhistone nuclear proteins (NHNP) were isolated from the hearts of hamsters in the myolytic, hypertrophic, and failing phases of cardiomyopathy and from paired controls. These proteins were solubilized in phenol and fractionated by polyacrylamide gel electrophoresis. One-dimensional gel electrophoresis, using either isoelectrofocusing or sodium dodecyl sulfate, showed quantitative differences between the dystrophic hearts and the controls. A high resolution of NHNP was achieved by two-dimensional gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 32 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…They were characterized by isoelectric points of 5.1 (A,) and 4.9 (A 2 ) and molecular weights of 60,000 and 25,000, respectively. We demonstrated in the preceding paper 26 that there were striking differences in NHNP between the control and the dystrophic hearts. Protein (A,) appears to correspond to protein (P 2 ) in our previous report.…”
Section: Identification Of Phosphorylated Nhnp By Two-dimensional Polmentioning
confidence: 66%
See 2 more Smart Citations
“…They were characterized by isoelectric points of 5.1 (A,) and 4.9 (A 2 ) and molecular weights of 60,000 and 25,000, respectively. We demonstrated in the preceding paper 26 that there were striking differences in NHNP between the control and the dystrophic hearts. Protein (A,) appears to correspond to protein (P 2 ) in our previous report.…”
Section: Identification Of Phosphorylated Nhnp By Two-dimensional Polmentioning
confidence: 66%
“…In an earlier study, we demonstrated alterations in NHNP composition of myocardium from patients with muscular subaortic stenosis as compared to those with infundibular hypertrophy or controls. 25 In a previous report, 26 we showed that there are striking differences in NHNP between the hearts of cardiomyopathic hamsters and controls. This report deals with the covalent modification of heart NHNP at different stages of the development of the cardiomyopathy.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The electrophoretic patterns of both IH and normal were strikingly similar and clearly distinct from that of MSS. Furthermore, we have shown that the NHNP profile obtained from purified cardiac muscle cells of failing cardiomyopathic hamsters did not differ significantly from that obtained from unpurified whole heart nuclei (Liew and Sole, 1978a).…”
Section: Figure 2 Fractionation Of Heart Nucleohistone Nucleohistonementioning
confidence: 79%
“…The pellet was resuspended once with Medium A, recentrifuged, then suspended in 30 ml of 2.2 M sucrose containing 1 mM MgCl 2 ,10 mM Tris-HCl (pH 8.0), and 0.1 mM PMSF and underlaid with 5 ml of the same solution. This suspension was centrifuged at 25,000 rpm for 1 hour in a Beckman SW 27 rotor as described previously (Taylor and Liew, 1976;Liew and Sole, 1978a). The pellet then was suspended in Medium A and centrifuged at 2000 rpm in the IEC centrifuge prior to fractionation of the nuclear proteins.…”
Section: Isolation Of Nucleimentioning
confidence: 99%